1981
DOI: 10.1210/jcem-53-1-135
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Positive Feedback on Gonadotropin Release in Estrogen-Primed Postmenopausal Women: Central Nervous System and Pituitary as Possible Sites of Action*

Abstract: To investigate the site and mode of action of progesterone in inducing gonadotropin release, the effects of catecholamine-depleting (methyldopa) or dopamine agonist (bromocriptine) drugs on progesterone positive feedback and the gonadotropin response to a centrally acting noradrenergic drug (clonidine) were evaluated in estrogen-primed postmenopausal women. Progesterone administration induced a significant rise in LH, FSH, and PRL serum levels in the control group. Bromocriptine administration was followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Hormone assay and analysis of data Serum T3, T4 and Prl were measured bv specific radioimmunoassavs as previously described (Nicoletti et al 1981). Thvroglobiilin and thvroid-microsomal anti¬ bodies were evaluated by commercial haemagglutination tests (Thymune M and Thymune T, Wellcome, Beckenham, England).…”
Section: Methodsmentioning
confidence: 99%
“…Hormone assay and analysis of data Serum T3, T4 and Prl were measured bv specific radioimmunoassavs as previously described (Nicoletti et al 1981). Thvroglobiilin and thvroid-microsomal anti¬ bodies were evaluated by commercial haemagglutination tests (Thymune M and Thymune T, Wellcome, Beckenham, England).…”
Section: Methodsmentioning
confidence: 99%
“…Our data do not agree, therefore, with the conclusions by Quigley et al [21] who observed LH release after DA-antagonist administration in women with prolacti noma. Although it is possible that the con current inhibition of norepinephrine synthe sis induced by AMPT [36,37] is responsible for the lack of gonadotropin response to the fall in DA neurotransmission in our subjects, since it has been demonstrated that nor adrenergic pathways stimulate gonadotropin secretion in both animal models [41][42][43] and humans [44], it must be underlined that neither Elli et al [35] nor Ambrosi et al [22] were able to show significant rises in serum LH after sulpiride or metoclopramide ad ministration in hyperprolactinemic patients. These and our data seem to negate, therefore, the possibility that DA hyperactivity in the hypothalamus inhibits gonadotropin secre tion in hyperprolactinemia.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to represent further proof against the hypothesis that DA hyperactivity at the Gn-RH-secreting terminals in the median eminence accounts for the impaired go nadotropin dynamics in hyperprolactinemic states. The lack of variations in gonadotropin concentrations during EPI infusion does not question, on the other hand, the possibility that adrenergic neurons are involved, at higher levels, in the control of gonadotropin release [41][42][43][44]54], since EPI does not cross the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Increased GH secretion is a well known endocrine consequence of clonidine administration in healthy individuals (3, 4, 5, 6,8,9,10,11,12,13,14). Thus intravenous or oral administration of 150-300 pg clonidine raises peripheral GH levels to a peak value 6-10 times higher than the pretreatment level after 50-90 min, depending upon the mode of administra-Key words: Clonidine, steroid hormones, peptide hormones, man tion (3, 4,9,11,12).…”
Section: Growth Hormone (Gh)mentioning
confidence: 99%